Physical Properties of Hyperluminous, Dust-obscured Quasars at z ∼ 3: Multiwavelength Spectral Energy Distribution Analysis and Cold Gas Content Revealed by ALMA - Sun, Weibin; Fan, Lulu; Han, Yunkun; Knudsen, Kirsten K.; Chen, Guangwen; Zhang, Hong-Xin (The Astrophysical journal, 2024)
We present a UV to millimeter spectral energy distribution (SED) analysis of 16 hyperluminous, dust-obscured quasars at z ∼ 3, selected by the Wide-field Infrared Survey Explorer. We aim to investigate the physical properties of these quasars, with a focus on their molecular gas content. We decompose the SEDs into three components: stellar, cold dust, and active galactic nucleus (AGN). By doing so, we are able to derive and analyze the relevant properties of each component. We determine the molecular gas mass from CO line emission based on Atacama Large Millimeter/submillimeter Array (ALMA) observations. By including ALMA observations in the multiwavelength SED analysis, we derive the molecular gas fractions, gas depletion timescales, and star formation efficiencies (SFEs). Their sample median and 16th–84th quartile ranges are f gas ∼ 0.33 − 0.17 + 0.33 , t depl ∼ 39 − 28 + 85 Myr, and SFE ∼ 297 − 195 + 659 K km s −1 pc −2 , respectively. Compared to main-sequence galaxies, they have lower molecular gas content and higher SFEs, similar to quasars in the literature. This suggests that the gas in these quasars is rapidly depleted, likely as the result of intense starburst activity and AGN feedback. The observed correlations between these properties and the AGN luminosities further support this scenario. Additionally, we infer the black hole to stellar mass ratio and black hole mass growth rate, which indicate significant central black hole mass assembly over short timescales. Our results are consistent with the scenario that our sample represents a short transition phase toward unobscured quasars.